2010
DOI: 10.1051/0004-6361/200912536
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a planetary companion around the giant star γ1Leonis

Abstract: Aims. Our primary goal is to search for planets around intermediate mass stars. We are also interested in studying the nature of radial velocity (RV) variations of K giant stars. Methods. We selected about 55 early K giant (K0−K4) stars brighter than fifth magnitude that were observed using BOES, a high resolution spectrograph attached to the 1.8 m telescope at BOAO (Bohyunsan Optical Astronomy Observatory). BOES is equipped with I 2 absorption cell for high precision RV measurements. Results. We detected a pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…It is premature to discuss the origin of long-term variations until we have longer time-span observations covering several variability cycles. For completeness, we would like to mention two other exoplanethosting candidate K giant stars from our survey: γ 1 Leo (Han et al 2010) and α Ari (Kim et al 2006;Lee et al 2011). They also exhibit long-term variations of the RV residuals that are superimposed with short-term pulsational variability, which is well established from night-to-night observations.…”
Section: Orbital Fitsupporting
confidence: 60%
See 2 more Smart Citations
“…It is premature to discuss the origin of long-term variations until we have longer time-span observations covering several variability cycles. For completeness, we would like to mention two other exoplanethosting candidate K giant stars from our survey: γ 1 Leo (Han et al 2010) and α Ari (Kim et al 2006;Lee et al 2011). They also exhibit long-term variations of the RV residuals that are superimposed with short-term pulsational variability, which is well established from night-to-night observations.…”
Section: Orbital Fitsupporting
confidence: 60%
“…We have reported two new exoplanets (Han et al 2010;Lee et al 2011) and confirmed an exoplanet ) and an oscillating star (Kim et al 2006).…”
Section: Observations and Analysismentioning
confidence: 55%
See 1 more Smart Citation
“…We suspect that this bias was come from the temporary mis-alignments of the BOES echelle spectrometer. But, we did not find any BVS shift in the K-giant γ 1 Leo for the same observing epoch as where a planetary companion system was detected by using the same echelle spectrometer BOES (Han et al 2010). The RV code RVI2CELL takes any changes into account in the instrumental profile in calculations of RVs, and thus instrumental misalignment is not likely to have affected the RV data.…”
Section: Line Bisector Variationsmentioning
confidence: 52%
“…For K-giant stars specifically, only four out of 72 known stars harboring planets are members of stellar multiple systems: 11 Com (Liu et al 2008), γ 1 Leo (Han et al 2010), 91 Aqr (Mitchell et al 2013), and 8 UMi (Lee et al 2015). Finding planets in multiple star systems allows us to learn more about the processes of planetary formation and evolution.…”
Section: Introductionmentioning
confidence: 99%